Synthesis of hierarchically micro-mesoporous carbon nanospheres: Molecular insight into the role of hexamethylenetetramine on the pore architecture - Ran Yuan; Shuxia Yuan; Yu Yang; Chunxiang Lu; Guohua Sun; Shijie Wu; Xiaodan Ren; Hao Cui (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Effects of Tetraselmis subcordiformis (Wille) Butcher with antimicrobial peptides as feed additives on gut microbial community and immunity of turbot (Scophthalmus maximus L.) - Bingkui Zhu; Fengjie Sun; Zhengquan Gao; Ting Yao; Subing Han; Hao Zhang; Yuyang Ma; Yuyong Wu; Ran Du; Chunxiao Meng; Yulin Cui (Journal of Applied Phycology, 2024)

First-principles design of noble metal (Rh and Pd) dispersed Janus WSTe monolayer for toxic gas sensing applications - Hao Cui; Mingxin Ran; Xiaoyan Peng; Guozhi Zhang (Journal of Environmental Chemical Engineering, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Efficient oxidation of ammonium to nitrogen gas via accelerated ClO• generation at TiO2/Ru-IrO2 bifacial electrode in a UV-driven photoelectrochemical system - Yi Liu; Ran Mao; Jingwei Hao; Kaifeng Wang; Ke Hu; Yuexin Cui; Xu Zhao (Chemical Engineering Journal, 2023)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

mTOR deletion ameliorates CD4 + T cell apoptosis during sepsis by improving autophagosome-lysosome fusion - Hao Wang; Guangxu Bai; Jianwei Chen; Wen Han; Ran Guo; Na Cui (Apoptosis, 2022)
Autophagy dysfunction contributes to CD4 + T cell apoptosis during sepsis leading to impairment of adaptive immunity. However, the underlying mechanism is unclear. The mammalian target of rapamycin (mTOR) pathway modulates CD4 + T cell survival during sepsis through mechanisms that are not fully understood. We developed a mouse model of sepsis through cecal ligation and puncture (CLP) to investigate dynamic changes in autophagy in CD4 + T cells. We used T cell specific-mTOR/tuberous sclerosis complex 1 (TSC1)-knockout mice to explore the roles of the mTOR pathway in modulating autophagy during sepsis. We observed reduced fusion of autophagosomes with lysosomes in the CD4 + T cells of CLP mice, which may represent a characteristic feature of autophagy dysfunction. Deletion of mTOR relieved autophagosome-lysosome fusion dysfunction and ameliorated apoptosis of CD4 + T cells in CLP mice, but this rescued phenotype was abolished by treatment with bafilomycin A1, a specific A-L fusion inhibitor. We further explored the underlying molecular mechanism and found that phosphorylation levels of transcription factor EB were significant higher in CLP mice and that expression of A-L fusion protein SNAREs were restricted, both of which were ameliorated by mTOR deletion. Taken together, these results suggest that the mTOR pathway plays a critical role in regulation of CD4 + T-cell apoptosis during sepsis, partly through regulation of A-L fusion-related protein transcription.

Terrestrial N 2 O emissions and related functional genes under climate change: A global meta‐analysis - Linfeng Li; Zhenzhen Zheng; Weijin Wang; Joel A. Biederman; Xingliang Xu; Qinwei Ran; Ruyan Qian; Cong Xu; Biao Zhang; Fang Wang; Shutong Zhou; Lizhen Cui; et al. (Global Change Biology, 2020)
Nitrous oxide (N 2 O) emissions from soil contribute to global warming and are in turn substantially affected by climate change. However, climate change impacts on N 2 O production across terrestrial ecosystems remain poorly understood. Here, we synthesized 46 published studies of N 2 O fluxes and relevant soil functional genes (SFGs, that is, archaeal amoA , bacterial amoA , nosZ , narG , nirK and nirS ) to assess their responses to increased temperature, increased or decreased precipitation amounts, and prolonged drought (no change in total precipitation but increase in precipitation intervals) in terrestrial ecosystem (i.e. grasslands, forests, shrublands, tundra and croplands). Across the data set, temperature increased N 2 O emissions by 33%. However, the effects were highly variable across biomes, with strongest temperature responses in shrublands, variable responses in forests and negative responses in tundra. The warming methods employed also influenced the effects of temperature on N 2 O emissions (most effectively induced by open‐top chambers). Whole‐day or whole‐year warming treatment significantly enhanced N 2 O emissions, but daytime, nighttime or short‐season warming did not have significant effects. Regardless of biome, treatment method and season, increased precipitation promoted N 2 O emission by an average of 55%, while decreased precipitation suppressed N 2 O emission by 31%, predominantly driven by changes in soil moisture. The effect size of precipitation changes on nirS and nosZ showed a U‐shape relationship with soil moisture; further insight into biotic mechanisms underlying N 2 O emission response to climate change remain limited by data availability, underlying a need for studies that report SFG. Our findings indicate that climate change substantially affects N 2 O emission and highlights the urgent need to incorporate this strong feedback into most climate models for convincing projection of future climate change.

Structure–activity relationship investigation of coumarin–chalcone hybrids with diverse side-chains as acetylcholinesterase and butyrylcholinesterase inhibitors - Lu Kang; Xiao-Hui Gao; Hao-Ran Liu; Xue Men; Hong-Nian Wu; Pei-Wu Cui; Eric Oldfield; Jian-Ye Yan (Molecular Diversity, 2018)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)